Climate Change Utilization Strategies Through the Lens of Technology: A Scientific Review - Suryawijaya, Tito Wira Eka; Andono, Pulung Nurtantio; Yusianto, Rindra (Indonesian Green Technology Journal, 2024)
This study sheds light on the untapped potential of AI in addressing the complex climate change challenges, simultaneously promoting energy efficiency and sustainable development. Issues such as carbon emissions and global climate shifts demand sophisticated solutions, and AI emerges as a versatile tool across various domains, including industry, renewable energy, and meteorological predictions, offering promising resolutions. The research findings unequivocally demonstrate AI's ability to optimize energy consumption, simulate solar radiation, predict severe weather conditions, and contribute to overall sustainability efforts. Despite existing challenges, such as substantial costs and data shortages, the prospects presented by AI for improving energy efficiency and embracing renewable energy sources are notably promising. The novelty of this research lies in its emphasis on AI's pivotal role in energy, meteorology, and grid management, underscoring the imperative collaborative synergy among governmental bodies, industrial players, and research institutions to drive sustainable AI innovations. This study encourages a holistic approach to harnessing AI's potential for mitigating climate change impacts and fostering a more sustainable future.